Upaya Peningkatan Semangat Belajar Anak di Madrasah Diniyah Desa Kesugihan Pulung Ponorogo - Faiza Renaldi; Dyan Putri Ayu (Social Science Academic, 2025)
Madrasah Diniyah Takmiliyah is a non-formal Islamic education institution whose learning is carried out in the afternoon and its function is as a complement to Islamic Religious education for the community. In this study the problem at Madin Miftahul Ulum in Kesugihan Village was that children at MDTA were less enthusiastic and motivated to study religion resulting in children having a lack of understanding of religion. Therefore, the authors are interested in researching how the learning process and methods increase motivation to learn religion and how the effectiveness of the methods applied in increasing children's learning motivation, especially in class 1 MDTA Miftahul Ulum, Kesugihan village. Through the mind mapping learning method and Audio-visual learning media, students are expected to be more happy and enthusiastic in participating in learning activities in class, so that the material delivered by educators can be easily understood by students, of course with minimal time, funds and facilities. The research method used is field research with data collection techniques in the form of observation, interviews, and documentation. The results showed that the implementation of learning Islamic religious education at Madrasah Diniyah Takmiliyah Awwaliyah by using brain planning learning techniques and Audio Visual media, students were more happy and enthusiastic about participating in class learning, especially since grade 1 was still playing the universe, and trusted the material delivered by the teacher. (educators) can be easily perceived by students.